2014
DOI: 10.1007/s12026-014-8553-9
|View full text |Cite
|
Sign up to set email alerts
|

Expression, cloning, and IgE-binding of the full-length dust mite allergen Der f 8

Abstract: Dermatophagoides farinae, a domestic mite species, produces some of the most potent allergens that contribute to allergy in China and worldwide. We sought to clone and express the group 8 allergen of D. farinae (Der f 8) to investigate its IgE-binding reactivity. The full-length cDNA encoding Der f 8 was generated by using RT-PCR and 5' RACE, cloned into pCold-TF expression vector, confirmed by nucleotide sequencing, sub-cloned into pET-28b (+), and transfected into E. coli BL21 cells for expression. After pur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…We found that the Derf8 gene sequence was similar to glutathione S-transferase; the latter has a close relation to allergic asthma [7]. Published data show that 40.9% of mite allergic patients had Derf8specific IgE in the sera [8,9]. It suggests that Derf8 may play an important role in the induction of allergy.…”
Section: Introductionmentioning
confidence: 99%
“…We found that the Derf8 gene sequence was similar to glutathione S-transferase; the latter has a close relation to allergic asthma [7]. Published data show that 40.9% of mite allergic patients had Derf8specific IgE in the sera [8,9]. It suggests that Derf8 may play an important role in the induction of allergy.…”
Section: Introductionmentioning
confidence: 99%
“…The group 8 allergen (Der f 8) of D. farina was cloned and characterized by us; the DNA sequence is listed in the NCBI database (http://www.ncbi.nlm.nih.gov/nuccore/KM010011.1), from which we found that the gene sequence of Der f 8 was quite similar to the gene sequence of glutathione S-transferase; the latter has a close relation with the pathogenesis of allergic asthma [9]. Previous studies have shown that 40.9 % of mite allergic patients with asthma exhibited IgE reactivity to Der f 8 [10,11]. It reveals that Der f 8 is a significant allergen of mite allergy, but the role of Der f 8 leading to allergic disorders remains to be further investigated.…”
Section: Introductionmentioning
confidence: 70%
“…We and others previously reported that TIM4 played a critical role in the expansion of Th2 response and allergic disorders [12][13][14]. Clinical data show that Der f 8-specific IgE can be detected in the patients with mite allergy [10]. Yet, the mechanism of the over expression of TIM4 by DCs in allergic diseases is unclear.…”
Section: Introductionmentioning
confidence: 94%
“…PCR products were inserted into expression plasmid pET‐28a(+) vector and transformed into Escherichia coli BL21 (DE3). Expressed recombinant proteins were identified with SDS‐PAGE . Recombinant proteins were purified using HiTrap TALON (5 ml TALON Superflow, 28‐9537‐66; GE Healthcare, Little Chalfont, Buckinghamshire, United Kingdom) on AKTA Prime Plus (GE) and dialyzed with PBS buffer using SnakeSkin Dialysis Tubing (3500 MWCO, 68035, Lot No.…”
Section: Methodsmentioning
confidence: 99%